Construct-related Validity of the Preschool Sound Production Test in Indonesian-Speaking - Taruna, Rexsy; Jumiarti, Jumiarti; Sadiah, Hikmatun; Phandinata, Stella Rosalina (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The availability of a speech intelligibility test that is in accordance with Indonesian with good psychometric evidence is needed for clinical practice needs. This study aims to evaluation whether the Tes Produksi Bunyi Prasekolah (Preschool Sound Production Test) has evidence of construct validity. Seventy-eight preschool children were divided into three groups. Typical Groups I and II were children without speech sound disorder who lived in Jakarta and Padang. Group III was children with speech sound disorder. Participants in each group consisted of 26 children. Ten participants were 4 years old and 5 years old, and 6 participants were 6 years old for each group. Speech intelligibility, percentage of consonants correct, and percentage of vowels correct were assessed individually using the Preschool Speech Sound Production Test. Based on the analysis results, it was found that the speech intelligibility index in the SSD group was lower than in Typical Group I (MD = -43.9; p < .001) and Typical Group II (MD = -41.96; p < .001). Referring to the results obtained, it can be concluded that the Preschool Sound Production Test has construct validity.